"No-Touch" Enhancement Significantly Reduces the Risk of Infection-Related Failure in Immediate Breast Reconstruction. (June 2019) - Wilson, Henry B.
Abstract : Purpose: Infection rates in prosthetic breast reconstruction after mastectomy vary widely, ranging from 1% to 35%, with meta-analyses reporting average infection rates of greater than 5%. This infection rate of greater than 5% is unfortunate for one of today's most commonly performed plastic surgical procedures. In an attempt to reduce infectious events, the author developed a "no-touch" protocol for performing breast reconstruction with tissue expanders and acellular dermis (ADM). This approach utilizes a transparent barrier drape and self-retaining retractor system patterned after similar orthopedic and urologic techniques that have proven to significantly reduce infection of implanted prostheses. Our preliminary results published in 2015 showed a significant improvement in infection rates. With this study, we assess the impact of the no-touch technique on a much larger number of patients. Methods: Institutional review board approval was granted for a retrospective study of patients who underwent immediate breast reconstruction with tissue expanders and ADM from 2010 to 2017 by the author. Reconstructions prior to the institution of a no-touch protocol in 2014 were compared with those after the enhancement was instituted. A minimum of 60 days' follow-up was used to assess surgical complications. Demographic and outcome data were analyzed. Results: Immediate breast reconstruction with tissue expanders and ADM was performed on 133 patients (217 breasts) from 2010 to 2017. Sixty-nine patients (113 breasts) underwent reconstruction from 2010 to 2014 utilizing the traditional technique, and 64 patients (104 breasts) underwent reconstruction from 2014 to 2017 using the new no-touch enhancement applied by the author. Patients in both groups had similar demographics and comorbidity profiles. The only other technique variable besides the addition of no-touch was the trend toward the use of larger sizes of ADM in the later group (164 vs 108 cm 2 ). The rate of infection-related reconstructive failure dropped from 11.5% (13/113) to 1.9% (2/104) ( P = 0.0054) after institution of the no-touch protocol. Conclusions: Institution of a specific no-touch protocol to immediate breast reconstruction with tissue expanders and ADM lowered the risk of reconstructive failure due to infection 6-fold—11.5% to 1.9%. Comparative studies from other surgeons are encouraged. Abstract : Supplemental digital content is available in the text.